Persinggungan Kepemimpinan Transformational Dengan Kepemimpinan Visioner Dan Situasional - Zainal Panani; Achmad Patoni; Binti Maunah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The purpose of writing this article is to determine the intersection of transformational leadership with visionary and situational leadership. This research uses a type of library research. Library research is research carried out by reviewing various journals and related reference books. The results of his research show that the transformative leadership model is a leadership model that can be an alternative to be applied in the current organizational system with various organizational dynamics and changes in line with the increasingly high demands of society. This is in line with the need for leaders who are able to bring about change. Transformative leadership is a leadership model that is different from traditional leadership models which view the relationship between leaders and employees (leadership and followership) as based solely on reward and punishment. A visionary leader is also understood as a leader who has a clear vision and mission in the organization. He has the ability to predict future events and express them in a clear and measurable vision and mission. Visionary leaders are able to raise the enthusiasm of their members with their motivation and imagination, to make the organization more alive and growing. Another situational leadership model is known as the Situational Contingency leadership model which revises the behavioral approach which is considered unable to explain ideal leadership. This approach illustrates that the style developed depends on the leader himself, the support of his followers, and a conducive situation. By analyzing the basic motivations of their subordinates, leaders can place them in appropriate situations. Transformative, visionary and situational leadership models have several elements in common, both in terms of systems, processes and objectives of Islamic Education Management. From the system side, there are elements of education unit leaders, educators, education staff, and various other elements; It is hoped that they can synergize in a process that is conducive to achieving goals.